Decentralized Multi-Robot Cooperation with Auctioned POMDPs - Capitan, Jesus; Spaan, Matthijs; Merino, Luis; Ollero, Anibal (Proceedings of the International Conference on Automated Planning and Scheduling, 2014)
Planning under uncertainty faces a scalability problem when considering multi-robot teams, as the information space scales exponentially with the number of robots. To address this issue, this paper proposes to decentralize multi-robot Partially Observable Markov Decision Processes (POMDPs) while maintaining cooperation between robots by using POMDP policy auctions. Auctions provide a flexible way of coordinating individual policies modeled by POMDPs and have low communication requirements. Additionally, communication models in the multi-agent POMDP literature severely mismatch with real inter-robot communication. We address this issue by exploiting a decentralized data fusion method in order to efficiently maintain a joint belief state among the robots. The paper presents results in two different applications: environmental monitoring with Unmanned Aerial Vehicles (UAVs); and cooperative tracking, in which several robots have to jointly track a moving target of interest.